2013
DOI: 10.1175/bams-d-12-00203.1
|View full text |Cite
|
Sign up to set email alerts
|

A Multiscale Soil Moisture and Freeze–Thaw Monitoring Network on the Third Pole

Abstract: SCIENTIFIC BACKGROUND AND OBJECTIVES. As the highest plateau in the world, the Tibetan Plateau (TP) directly impacts its surrounding climate and environment through atmospheric and hydrological processes. Meanwhile, the TP climate changed significantly (such as rapid warming, moistening, solar dimming, and wind stilling) over the past 30 years , which further altered its environment (e.g., glacier retreat, lake expansion, and permafrost degradation, etc.) and brought environmental risks and disasters to the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
197
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 326 publications
(222 citation statements)
references
References 39 publications
2
197
1
1
Order By: Relevance
“…On one hand the AMSR-E soil moisture with rather coarse spatial resolution is a mixing contribution from different land surface elements, which may have smoothed out the spatial variability in land surface soil moisture. On the other hand, other studies have revealed that the AMSR-E soil moisture product exhibits underestimates [73,74]. The MOD16 ETa is overestimated in winter, whereas in the growing season, it is much lower than EC observations at these three sites, especially at the Yingke Oasis station (Figure 5a).…”
Section: Comparison With the Ground Measurementsmentioning
confidence: 61%
See 1 more Smart Citation
“…On one hand the AMSR-E soil moisture with rather coarse spatial resolution is a mixing contribution from different land surface elements, which may have smoothed out the spatial variability in land surface soil moisture. On the other hand, other studies have revealed that the AMSR-E soil moisture product exhibits underestimates [73,74]. The MOD16 ETa is overestimated in winter, whereas in the growing season, it is much lower than EC observations at these three sites, especially at the Yingke Oasis station (Figure 5a).…”
Section: Comparison With the Ground Measurementsmentioning
confidence: 61%
“…(2) The soil moisture data derived from passive microwave sensors, such as AMSR-E, Soil Moisture and Ocean Salinity (SMOS), and Fengyun-3 (FY-3) MicroWave Radiation Imager (MWRI) have a coarse spatial resolution (25 km), which is not sufficient for regional scale studies [73,74]. The accuracy and spatial resolution will improve in the near future [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…NASA is launching the Hydrosphere State Mission as part of the Earth System Science Pathfinder Program (ESSP) to improve satellite monitoring of global land freeze/thaw status and soil moisture (Entekhabi et al, 2004). In China, a multi-scale monitoring network has been established on the Qinghai-Tibetan Plateau (Yang et al, 2013). Fifty-six stations have been installed in cold and high-elevation regions to enhance monitoring of soil temperature and moisture and hence to support remote sensing data and large-scale climate modeling (Su et al, 2011;Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In China, a multi-scale monitoring network has been established on the Qinghai-Tibetan Plateau (Yang et al, 2013). Fifty-six stations have been installed in cold and high-elevation regions to enhance monitoring of soil temperature and moisture and hence to support remote sensing data and large-scale climate modeling (Su et al, 2011;Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, these retrieval methods perform poorly for estimating soil moisture values in cold regions such as the Tibetan Plateau (TP) area (Chen et al, 2013b;Su et al, 2011;Zeng et al, 2015), and only the value of a few centimeters depth can be derived, which is limited for many applications. Ground measurements are the most accurate soil moisture estimates, and huge efforts have been conducted to establish long-term and largescale soil moisture observation networks in several regions of the world (Dorigo et al, 2011;Yang et al, 2013). Nevertheless, it is still limited and far from sufficient in the TP area, because of the high spatiotemporal variability of soil moisture, the high economic cost and difficulties in practice.…”
Section: Introductionmentioning
confidence: 99%